Theology of Women's Liberation in the Perspective of Riffat Hasan; Ideas Toward the Reform of Indonesian Islamic Law - Hakiki, Kiki Muhamad; Rohmatika, Ratu Vina; Muttaqien, Zaenal; Badruzaman, Badruzaman (Universitas Islam Negeri Raden Intan Lampung, 2024)
Women's liberation theology, developed by Riffat Hassan, offers a critical hermeneutical approach to interpreting Islamic sacred texts in a way that is more inclusive and just towards women. Riffat Hassan's thinking highlights that many patriarchal interpretations that harm women come from the dominant social and cultural context, not from the text itself. This research uses a qualitative method with a content analysis approach. Through critical hermeneutic analysis, this research emphasizes the principles of justice, equality, and human dignity in Islam as a foundation for reforming religious understandings and practices that discriminate against women. In the context of Islamic law in Indonesia, this thinking is highly relevant to review and reform various aspects of family and civil law. Reforming inheritance, marriage and divorce laws based on the principles of gender justice can enhance the protection and rights of women. Riffat Hassan's opposition to all forms of violence against women provides a theological basis for strengthening stricter legal provisions. Increasing women's participation in leadership and politics is also supported through an egalitarian re-reading of religious texts. By adopting a more inclusive approach, Islamic law in Indonesia can be more responsive to social change and create a more just and equal system for women.